Proceedings of the 12th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management 2020
DOI: 10.5220/0010020200630075
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Virtual Reality as an Adaptable Boundary Object in the Design Phase of Facility Life Cycle

Abstract: Although the large majority of costs of buildings incur in the later operation and maintenance phase, major decisions affecting these costs are made in the early design and construction phases. Virtual Reality (VR) and Collaborative Virtual Reality (CVR) have been noticed to have significant potential in involving the expertise and needs of various stakeholders into the early design phases, increasing the quality of building designs and reducing related costs. Boundary Object Theory has been noticed useful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Finally I should mention that these ideas, though perhaps not in this form, are familiar in some of the literature in technology studies which is perhaps another natural habitat for stigmergic systems (see for example Lepola et al, 2020;Rambusch et al, 2004;Sellberg and Susi, 2014;Sismondo, 2012;Susi, 2006;Wickman, 2015) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally I should mention that these ideas, though perhaps not in this form, are familiar in some of the literature in technology studies which is perhaps another natural habitat for stigmergic systems (see for example Lepola et al, 2020;Rambusch et al, 2004;Sellberg and Susi, 2014;Sismondo, 2012;Susi, 2006;Wickman, 2015) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased feel of presence and immersion together with the ability to communicate verbally and non-verbally, collaboration in VR is understood as more efficient and flexible than the collaboration via traditional conferencing tools. Evidence has shown that VR is capable of positively affecting the elements of remote communication, such as the clarity and richness of communicated information, and enhance the quality of discussion and knowledge transfer due to shared context and awareness of others [22][23][24].…”
Section: Collaborative Vrmentioning
confidence: 99%